2017
DOI: 10.18203/issn.2455-4510.intjresorthop20170789
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between aperture and suspensary fixation of hamstring autografts on femoral side in ACL reconstruction: clinical and radiological outcome assessment

Abstract: <p class="abstract"><strong>Background:</strong> Arthroscopically aided anterior cruciate ligament reconstruction using hamstring graft can be fixed to femoral condyle by suspensory and aperture fixation methods. The following study was undertaken to investigate whether there is any difference in functional outcomes with these fixation methods as measured by the Lysholm knee score and to determine tunnel widening post operatively with these two methods and does it affect the functional outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…While in the aperture fixation group (n = 20), it was 43.85±6.47 pre-operatively and 87.7±4.85 at the end of six months post-operatively. On intergroup comparison using independent t-test, aperture fixation was found to increase the Modified Tegner Lysholm Knee Score than suspensory fixation, which is in agreement with a study conducted by Kashid MR et al [8] However, the difference was not statistically significant. Modified Tegner Lysholm Knee Score has a significant role in assessing the improvement or deterioration of knee function and activity level.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While in the aperture fixation group (n = 20), it was 43.85±6.47 pre-operatively and 87.7±4.85 at the end of six months post-operatively. On intergroup comparison using independent t-test, aperture fixation was found to increase the Modified Tegner Lysholm Knee Score than suspensory fixation, which is in agreement with a study conducted by Kashid MR et al [8] However, the difference was not statistically significant. Modified Tegner Lysholm Knee Score has a significant role in assessing the improvement or deterioration of knee function and activity level.…”
Section: Discussionsupporting
confidence: 89%
“…When suspensory fixation and aperture fixation techniques were compared, as summarized in Table 2, the Modified Tegner Lysholm Knee Score was more effectively reduced with aperture fixation than with suspensory fixation at one month and six months post-operatively, but the difference was not statistically significant. Studies have demonstrated similar kinds of results with suspensory and aperture fixation techniques in the context of the improvement of Lysholm Knee Scores [8,13,24] . Ping et al conducted a prospective study using Lysholm, International Knee Documentation Committee (IKDC), and Larson scoring with an average follow up of 29.5 months and found no statistically significant scoring differences between groups at the end of follow up period, which is in accordance with our results [25] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation